PENGARUH MODEL EXPERIENTAL CREATIVE LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF ANAK USIA 4-5 TAHUN DI TK KARUNIA SURABAYA - Intan Bharul Azzahra Putri; Yes Matheos Malaikosa (Jurnal Manajemen Pendidikan, 2026)
Creative thinking ability is an important aspect that needs to be developed from an early age, but learning practices in kindergartens are still often dominated by conventional approaches that do not provide meaningful learning experiences. This study aims to analyze the effect of the Experiential Creative Learning Model on the creative thinking ability of children aged 4–5 years at Karunia Kindergarten Surabaya. The study used a quantitative approach with a quasi-experimental method through an experimental group design and a control group. Data were collected using observations and assessments of creative thinking abilities through learning activities designed based on the Experiential Creative Learning syntax, then analyzed using the Independent Sample t-test. The results showed that the average post-test score of the experimental group (92.13) was higher than the control group (84.11). The hypothesis test produced a t value = 4.587 with a significance of 0.000 (p < 0.05), which indicates a significant difference between the two groups. These findings prove that the application of the Experiential Creative Learning Model has a positive and significant effect on improving the creative thinking ability of children aged 4–5 years. Thus, this model can be an alternative effective learning strategy to create an active, fun, and child-centered learning environment to optimize the development of creativity in early childhood education.